2016
DOI: 10.1038/ejhg.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray testing in adults with intellectual disability presenting with comorbid psychiatric disorders

Abstract: Chromosomal copy-number variations (CNVs) are a class of genetic variants highly implicated in the aetiology of neurodevelopmental disorders, including intellectual disabilities (ID), schizophrenia and autism spectrum disorders (ASD). Yet the majority of adults with idiopathic ID presenting to psychiatric services have not been tested for CNVs. We undertook genome-wide chromosomal microarray analysis (CMA) of 202 adults with idiopathic ID recruited from community and in-patient ID psychiatry services across En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
2
17
0
4
Order By: Relevance
“…Previous investigations in this patient group identified a diagnostic yield of 11% CNVs classed as clinically relevant. 19 In this study, utilising data from three European research sites, we replicate this finding with a higher diagnostic yield of 13.0% pathogenic CNVs in 599 participants (or 13.9% with the previously reported cases removed). Given that CMA is being advocated for use in cohorts with schizophrenia, in which the diagnostic yields are lower (between 2.5 and 5%), 34,35 adults with intellectual disabilities presenting to psychiatric services appear to be a group to prioritise for CMA.…”
Section: Main Findingssupporting
confidence: 65%
See 1 more Smart Citation
“…Previous investigations in this patient group identified a diagnostic yield of 11% CNVs classed as clinically relevant. 19 In this study, utilising data from three European research sites, we replicate this finding with a higher diagnostic yield of 13.0% pathogenic CNVs in 599 participants (or 13.9% with the previously reported cases removed). Given that CMA is being advocated for use in cohorts with schizophrenia, in which the diagnostic yields are lower (between 2.5 and 5%), 34,35 adults with intellectual disabilities presenting to psychiatric services appear to be a group to prioritise for CMA.…”
Section: Main Findingssupporting
confidence: 65%
“…We previously reported a rate of 11% pathogenic CNVs in a subset of 202 of the 247 participants from the England sample. 19 When these 202 individuals are removed from the combined sample the diagnostic yield is 13.9%, thus replicating the initial finding.…”
Section: Pathogenic Cnv Yieldsupporting
confidence: 55%
“…Additionally, patients with 2q13 CNVs on the DatabasE of genomiC varIation and Phenotype in Humans using Ensembl Resources (DECIPHER) database (https://decipher.sanger.ac.uk/) were identified and further phenotypic information was sought from responsible clinicians. One participant was also included from a previous investigation of CNVs in adults recruited from ID psychiatry services (Wolfe et al, ). Informants or clinicians were asked whether the participant had taken place in previous research projects, and to the best of our knowledge none of the other patients have been presented in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research found that around 10% of adults with presumed idiopathic intellectual disability presenting to psychiatric services had likely neurosusceptibilty variants, with deletions and duplications at 15q11‐q13 and 16p11.2‐p13.11 being most frequently observed (Wolfe et al, ). Other recent research has shown that patients with schizophrenia and neurosusceptibilty variants were significantly more likely to have lower IQs (Lowther et al, ).…”
Section: Literature Review Of Genetic Testing For People With Intellementioning
confidence: 99%